METALANGUAGE THEORY: INTERPRETATION OF ZI-SHU-NV’S MARRIAGE BELIEF - Zhang Suojun; Zoya D. Astatyan (Russian Studies in Culture and Society, 2022)
The relevance of the study is determined by the necessity to understand the mechanisms of formation within a society of socially significant ideas, beliefs and behavioral strategies.